INDONESIA’S DEATH PENALTY EXECUTION FROM THE REALIST VIEW OF INTERNATIONAL LAW - Azmi, Alia (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
During the first half of 2015, Indonesia executed fourteen prisoners who had been convicted of smuggling drugs to and from Indonesia. Twelve of them were foreigners. This execution led to withdrawal of the ambassador of Brazil, Netherlands, and Australia, whose citizens are among those executed. Criticism came from around the world, and small number of Indonesians. Most critics cited human rights abuse; and death penalty is against international law. However, the lack of further explanation can make the statement misunderstood. The distinctive nature of international law is one factor that makes death penalty issue is still debatable. Another factor is the inconsistent world’s reaction on human rights issues, showing realistic behavior in international relations. Therefore it is important to understand the nature of international law from the realist perspective of international relations in explaining death penalty in Indonesia. The purpose of this paper is to elaborate Indonesia’s death penalty from the realist perspective of international law.Keywords: realism, international law, international relations, death penalty